2019
DOI: 10.1515/jbnst-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

The German Statutory Minimum Wage and Its Effects on Regional Employment and Unemployment

Abstract: This paper studies the effects of the introduction of Germany’s statutory minimum wage in 2015 on employment and unemployment on the level of regional labor markets. Using variation in the regional exposure to the new wage floor, we employ a difference-in-differences approach that compares the evolution of employment and unemployment between regions with varying minimum wage bites. Overall, we find no statistically significant effect of the introduction of the German minimum wage on regular employment subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
2
14
0
2
Order By: Relevance
“…Another German study found rather similar results (Bonin et al 2019). After two years there had been a reduction of marginal employment, but the researchers could not confirm any significant changes in regular employment and unemployment.…”
Section: Statutory Minimum Wages In Europe: a Brief Backgroundsupporting
confidence: 60%
See 1 more Smart Citation
“…Another German study found rather similar results (Bonin et al 2019). After two years there had been a reduction of marginal employment, but the researchers could not confirm any significant changes in regular employment and unemployment.…”
Section: Statutory Minimum Wages In Europe: a Brief Backgroundsupporting
confidence: 60%
“…Some recent research in Europe covers the relationship between statutory minimum wages and such aspects as working hours and employment (Eurofound 2019a: 34). We have access to new studies on these topics in Germany, Greece and Ireland (Bonin et al 2019;Bruttel 2019;Caliendo et al 2018;Georgiadis et al 2018;McGuiness and Redmond 2018). The general result is that the impact on employment has been small.…”
Section: Statutory Minimum Wages In Europe: a Brief Backgroundmentioning
confidence: 99%
“…In contrast, Ahlfeldt et al (2018) and Dustmann et al (2019) do not find any discernible effects on total employment using regional-level data if they account for region-specific differences in employment trends prior to the reform. Other studies that use regional wage variation distinguish between regular and marginal employment and identify negative effects; however, usually, only the effect on marginal employment is precisely estimated (Bonin et al 2019;Caliendo et al 2018;Schmitz 2019). According to this set of studies, between 70,000 and 200,000 marginal jobs have been lost due to the introduction of the minimum wage.…”
Section: Effects Of the German Minimum Wage On Employmentmentioning
confidence: 99%
“…Germany from second position to the seventh one moved within three years, it means that range of regulations were wider in 2016. The drop in the ranking was the effect of introduction of statutory minimum wage as one of the most significant institutional change in Germany after ' Hartz' reforms in 2003-2005(Bonin et al, 2020.…”
Section: Resultsmentioning
confidence: 99%